Groundwater lowering in construction : a practical guide to dewatering - Cashman, P. M. (Pat M.); Preene, M. (Martin) (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
Praise for the Second Edition: "This is the book that the dewatering sector really needs - it is reliably based on sound theory and profound understanding of the physical processes, yet is presented in a very accessible and user-friendly manner. It draws on many, many decades of experience, and yet is utterly up to date. . . . It is a one-stop shop for the dewatering practitioner - who can nonetheless rest assured that the theoretical basis of the methods presented is flawless."-- Professor Paul L. Younger, FGS, FICE, C.Geol., C.Eng., FREng, University of Glasgow, Scotland, UK "The best reference on this topic available . . . and will prove useful to a wide variety of readers ranging from junior construction engineers or dewatering contractors to theoretical hydrogeologists and environmental managers. It is rare that a book is able to bridge the gap between theoretical design guidance and practical application." -- S.N. Sterling, University of Waterloo, Canada The extensively updated Groundwater Lowering in Construction: A Practical Guide to Dewatering, 3rd Edition offers practical advice on all phases of groundwater control systems, from planning and design, through installation and maintenance, and ultimately decommissioning. The expertise provided in this book can help you improve working conditions, increase project viability, save time and reduce excavation costs. Designers and managers of construction and engineering projects are given the tools necessary to effectively control groundwater. The content is divided into three sections - Principles, Design and Construction. The Principles section explains the fundamentals of groundwater flow as it relates to civil engineering excavations. The Design section explores in extensive detail site investigation, permeability assessment methods and groundwater control strategies. Chapters in the Construction section describe dewatering and exclusion techniques, and examine the complete life cycle of a groundwater control scheme, including monitoring, maintenance and decommissioning. This section incorporates eleven case histories from the authors' casebook. The 3rd edition has been greatly revised and updated, and contains more than 200 new illustrations. The new content covers: Permeability of soils and rocks Groundwater problems for excavations in rock Groundwater control for tunnelling projects, such as shafts and cross passages Methods for assessing permeability Decommissioning of dewatering systems Optimisation of groundwater control schemes. The new, expanded content offers valuable direction that can give you a true competitive advantage in the planning and execution of temporary and permanent dewatering works for excavation and tunnelling. Written for practising engineers, geologists and construction managers, as well as postgraduate engineering students, this revamped manual on design and practice presents numerous case studies and extensive references to enhance understanding. Martin Preene is a groundwater consultant, based in the UK. He has more than 30 years' experience working on dewatering and groundwater control projects worldwide.The late Pat Cashman was the leading British exponent of groundwater control for his generation, championing a practical and straightforward approach for more than forty years.
OCLC-licensed vendor bibliographic record.
Keywords: Earthwork; Drainage; Building sites; Groundwater flow; Water table; Zone of aeration; SCIENCE / Environmental Science